Classes of analytic functions involving the q-Ruschweyh operator and q-Bernardi operator - Khadeejah Rasheed Alhindi; Khalid M. K. Alshammari; Huda Ali Aldweby (AIMS Mathematics)
In this paper, we introduced and studied two new classes of analytic functions using the concepts of subordination and q-calculus. We established inclusion relations for these q-classes and integral-preserving properties associated with the q-integral operator. We also determined certain convolution properties.